2021
DOI: 10.3390/ijms221910586
|View full text |Cite
|
Sign up to set email alerts
|

ADSC-Based Cell Therapies for Musculoskeletal Disorders: A Review of Recent Clinical Trials

Abstract: Recently published clinical trials involving the use of adipose-derived stem cells (ADSCs) indicated that approximately one-third of the studies were conducted on musculoskeletal disorders (MSD). MSD refers to a wide range of degenerative conditions of joints, bones, and muscles, and these conditions are the most common causes of chronic disability worldwide, being a major burden to the society. Conventional treatment modalities for MSD are not sufficient to correct the underlying structural abnormalities. Hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 243 publications
(274 reference statements)
1
15
0
1
Order By: Relevance
“…To rule out these interferences, we only counted Collagen X positive cells in the cartilage region (within the red dash box, Figure 3A ). In clinic, intra-articular administration of either autologous or allogeneic ADSCs has been reported to relieve pain and promote cartilage regeneration in OA patients, without any treatment-related severe adverse events ( Lee et al, 2021 ; Maheshwer et al, 2021 ). For example, in a clinical trial on autologous ADSCs into the knee, the VAS and the WOMAC pain scores at 6 months post-treatment significantly decreased by 45 and 39% (each p < 0.01 vs. baseline) in the high-dose group (1 × 10 8 cells), respectively ( Jo et al, 2014 ), while not in the low-dose group (1 × 10 7 cells).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To rule out these interferences, we only counted Collagen X positive cells in the cartilage region (within the red dash box, Figure 3A ). In clinic, intra-articular administration of either autologous or allogeneic ADSCs has been reported to relieve pain and promote cartilage regeneration in OA patients, without any treatment-related severe adverse events ( Lee et al, 2021 ; Maheshwer et al, 2021 ). For example, in a clinical trial on autologous ADSCs into the knee, the VAS and the WOMAC pain scores at 6 months post-treatment significantly decreased by 45 and 39% (each p < 0.01 vs. baseline) in the high-dose group (1 × 10 8 cells), respectively ( Jo et al, 2014 ), while not in the low-dose group (1 × 10 7 cells).…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of another control group of animals without OA induction but injection of ADSCs to examine the effect of ADSCs in healthy joint would have added more strength to the study. As the primary goal of this study is to evaluate the anti-OA efficacy of ADSCs, and a series of clinical studies have demonstrated the safety of intra-articular injection of ADSCs ( Lee et al, 2021 ; Maheshwer et al, 2021 ), we avoided the excessive use of animals by adding a 4 th (additional control) group. Although we demonstrated the anti-OA efficacy of ADSCs and ADSCs-CM in the OA rat model, which bioactive component plays the major anti-OA role, and whether there are synergistic effects within the ADSCs secretome are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were excluded if they had (1) knee pain from causes different than OA (i.e., tumors or referred pain from the hip or lumbar spine); (2) previous surgery within the last 12 months; (3) previously received mesenchymal cell therapy due to any medical condition; (4) displaced meniscal tear on MRI; (5) grade IV chondral defect on MRI; (6) previous knee intra-articular injectable therapy within the last 6 months; (7) coagulation disorders (i.e., hemophilia); (8) a history of cancer; (9) a history of systemic illness or significant organ impairment/failure (i.e., renal failure); (10) a history of atypical chronic pain syndrome (i.e., chronic regional pain); (11) a history of allergy to any substances used within the treatments; and/or (12) being pregnant or breastfeeding.…”
Section: Participantsmentioning
confidence: 99%
“…First described in 2001, adipose-derived stromal cells (ASCs) are easy to harvest and include a higher proportion of MSCs, particularly after expansion. [12][13][14][15][16] Previous studies have reported that intra-articular injections of expanded ASCs may improve cartilage quality and delay OA progression. [17][18][19] However, there is a lack of comparative studies evaluating PRP with expanded ASCs.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9]. Equally important is the ability to obtain the required number of autologous cells at any age, preventing graft rejection reactions, the risk of transmissible infections, and avoiding many legal and ethical limitations of cell therapy [10].…”
Section: Introductionmentioning
confidence: 99%